GREEN MARKETING AND REPRESENTATION OF THE OTHER (An Analysis of Green Image Ad Represented by Teh Kotak Ad, ‘Persembahan dari Alam’ Version) - Tangguh Okta Wibowo (Profetik: Jurnal Komunikasi, 2017)
This paper presents a theoretical link among green marketing of Teh Kotak ad, “Persembahan dari Alam” version. This is an ad telling as if the product of Teh Kotak is truly from nature. In addition, this research explored the portrayal of how this ad contains metaphorical element to juxtapose nature and technology as the same level. In the analysis, this study attempts to use Green marketing theory as a tool for analysis to explore what is the message behind the ad. Moreover, exploring the representation of the portion of the position of gender where the ad uses a woman as the main actor picking tea leaf, as if this ad looks natural. The result of the study revealed that Green marketing showed it competences to cover with political agenda. It is reflected in green image which told that The Kotak is a gift from nature. Overall, this study concludes that green image of this ad relays the hidden meaning, where the main aim is inviting people to buy its product as political agendas.